Entrelaços: proposta de protocolo de pré-natal psicológico para os centros de saúde da família de Sobral-Ce - Brito Neto, Cláudio Soares (2023)
Pregnancy, childbirth and postpartum are stages in a woman's life cycle that cause adaptations, changes in identity and redefinitions of roles that are often risk factors for women's mental health and healthy development. of motherhood. This research consists of presenting and validating the content of the “ENTRELAÇOS” intervention protocol as an action proposal for the Family Health Centers of Sobral - CE. Based on the Psychological Prenatal Model (PNP), analyzed through an integrative review of the literature, the protocol was designed with the aim of strengthening comprehensive care for women's health during pregnancy, with an emphasis on the importance of attention to psychological aspects and emotional aspects of the period. This study consists of three subsequent stages: the integrative review, which includes the data collection and analysis stage for preparing the protocol; the construction of the protocol and; the third stage, with the presentation of the protocol for initial content validation by judges. This study is an exploratory and methodological research with a subsequent mixed approach. The results were analyzed using the Content Validity Index (CVI) and demonstrate a 98% level of agreement between judges on the content of the instrument. As a technical and bibliographic product resulting from this research, a literature review article was produced, the “ENTRELAÇOS” protocol and, subsequently, it is intended to publish an article with the results of this research.